Two new species of Echinoderes (Kinorhyncha: Cyclorhagida) from the Gulf of Mexico - Sørensen, Martin V.; Landers, Stephen C. (Frontiers in Marine Science, 2014)
Comprehensive sampling of meiofauna along the northern continental slope in the Gulf of Mexico has revealed a diverse kinorhynch fauna of undescribed species. The present contribution includes the description of two new species of the cyclorhagid genus Echinoderes. Echinoderes augustae sp. nov. is recognized by the presence of acicular spines in middorsal positions on segments 4 to 8, and in lateroventral positions on segments 6 to 9, tubes in lateroventral positions on segments 2 and 5, midlateral positions on segment 4, and in sublateral positions on segment 8. It furthermore has glandular cell outlets type 2 in subdorsal positions of segment 2, a middorsal protuberance-like extension from the intersegmental border between segments 10 and 11, and conspicuously short and stout lateral terminal spines. Echinoderes skipperae sp. nov. has acicular spines in middorsal positions on segments 4, 6 and 8, and in lateroventral positions on segments 8 and 9, tubes in sublateral and ventrolateral positions on segment 2, in lateroventral positions on segment 5, in lateral accessory positions on segment 8, and in laterodorsal positions on segment 10. The species can furthermore be recognized by its conspicuously well-developed pachycycli at the anterior segment margins of segments 2 to 10, and margins of sternal plates facing the midsternal junctions of segments 3 to 10.